2002
DOI: 10.1002/ijc.10606
|View full text |Cite
|
Sign up to set email alerts
|

BXD recombinant inbred mice represent a novel T cell–mediated immune response tumor model

Abstract: To develop a better animal model for studying the effects of the host environment in neoplasia, we injected various genetically well-characterized H-2 d RI strains of BXD mice with syngeneic breast cancer cells (TS/A) and monitored the growth of tumors over time. There was a marked difference in the growth of the implanted breast cancer cells among the 14 BXD RI strains, with 4 patterns of tumor development being observed: in type I, the implanted tumor cells grew rapidly in the first 2 weeks, necrosis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 77 publications
3
20
0
Order By: Relevance
“…An allograft from the syngeneic breast cancer cell line (TS/A) derived from a mammary adenocarcinoma that arose spontaneously in a BALB/c female mouse was also used. These latter cells (TS/A) were implanted in a BXD mouse, a genetically well-characterized animal model for studying the host immune response to neoplasia (Grizzle et al 2002). Normal lung tissues from corresponding athymic mice and BXD RI mice also were processed as control samples.…”
Section: Cell Linessupporting
confidence: 42%
“…An allograft from the syngeneic breast cancer cell line (TS/A) derived from a mammary adenocarcinoma that arose spontaneously in a BALB/c female mouse was also used. These latter cells (TS/A) were implanted in a BXD mouse, a genetically well-characterized animal model for studying the host immune response to neoplasia (Grizzle et al 2002). Normal lung tissues from corresponding athymic mice and BXD RI mice also were processed as control samples.…”
Section: Cell Linessupporting
confidence: 42%
“…We have concomitantly observed that, at 12 months of age, the female B Â D RI strains with a slow rate of thymic involution also exhibited low tumor growth followed by regression of the tumor and an increased production of IFN-g in response to the TS/A breast tumor cells. 39 These results therefore suggest that identification of the genetic loci influencing the onset and rate of age-related thymic involution may be relevant to age-related immune defects and other associated diseases, such as cancer. We are currently analyzing the gene expression data and establishing F2 and congenic mice to narrow down the intervals of the QTL mapping results.…”
Section: Discussionmentioning
confidence: 46%
“…1a) was correlated with a lower resistance to growth of P1A-expressing tumors (results not shown). Whether differences in the efficacy of CD8 T cell selection also contribute to the higher susceptibility of DBA/2 as compared with C57BL/6-based mice in other transplanted tumor models (46) remains to be addressed.…”
Section: Discussionmentioning
confidence: 48%